Establishing a Staging System for Adjacent Segment Disease and Exploring Its Significance in Guiding Surgical Decisions: A Retrospective Study - Changpeng Qu; Jianwei Guo; Hao Tao; Chuanli Zhou; Kai Zhu; Yihao Sun; Lei Li; Zhiming Liu; Hao Zhang; Xuexiao Ma (Orthopaedic Surgery)
ABSTRACT Objective The degeneration characteristics of adjacent segment disease are complex. Improper surgical planning has caused unnecessary surgical trauma and costs. The purpose of this study was to establish a staging system for adjacent segment disease and evaluate its guiding significance for surgical decisions in adjacent segment disease. Methods A retrospective study was performed on 103 patients with adjacent segment disease who underwent treatment between January 2017 and January 2023. Based on radiological findings, adjacent segment disease was categorized into four stages, with no cases identified in Stage IV. Patients were divided into four intervention groups: Group A (control group, traditional posterior lumbar fusion with rod‐screw revision), Group B (Stage I, percutaneous endoscopic decompression), Group C (Stage II, oblique lumbar interbody fusion), and Group D (Stage III, cortical bone trajectory screws with posterior lumbar interbody fusion). Clinical and radiological outcomes were evaluated postoperatively, at 3 months, and at 12 months. Statistical analysis was conducted using t‐tests, Mann–Whitney U tests, chi‐square tests, and Spearman's correlation. Results Surgical expenses, duration, estimated blood loss, postoperative hospital stays, disc height index, and Pfirrmann grading all demonstrated significant correlations with the established grading system (p < 0.05). Patients achieved favorable clinical outcomes. Specifically, Groups B, C, and D showed earlier functional recovery compared to Group A, with Groups B and C experiencing more rapid relief from low back pain. Furthermore, Groups B, C, and D had shorter surgical times and reduced blood loss, while Groups B and C also incurred lower surgical costs and shorter hospital stays (p < 0.05). Conclusion The new grading system, developed based on the characteristics of adjacent segment degeneration, showed excellent surgical adaptability, despite varying degrees of correlation across different factors. This system was closely linked to the degree of intervertebral disc degeneration and the intervertebral disc height index. All patients achieved favorable surgical outcomes, suggesting that this grading system could provide valuable guidance in making surgical treatment decisions.